The evolution of China’s English education policy and challenges in higher education: analysis based on LDA and Word2Vec - Hu, Haiyang; Li, Fan; Luo, Zhengying (Frontiers in Education, 2024)
China proposed the Belt and Road Initiative to strengthen regional connectivity so as to embrace a brighter future together. Since the Initiative was put forward, it has brought many challenges to China’s English education policy. By employing Latent Dirichlet Allocation (LDA) and Word2Vec, this study analyzes the evolution of topics and challenges in China’s English education policy under the Belt and Road Initiative. The results indicate that after the initiative, the policy focus has changed. English education has shifted from testing abilities to cultivating students’ intercultural communication skills in order to meet the needs with countries alongside the “Belt and Road”. Moreover, teaching strategies that were examination-oriented have also changed to emphasizing teaching methods and feedback. The focus and teaching strategies have also undergone great changes. China’s English education policy has shifted from focusing on improving students’ writing skills, English proficiency, and creativity to conducting in-depth research and addressing specific issues, including challenges in linguistics, media influence, educational institutions and programs, online courses, attitudes and self-efficacy, use of multiple languages and globalization, teaching issues, and curriculum design. These findings shed light on how the Belt and Road Initiative changed China’s English education policy and provide further directions for future research.